Fibrous shape underlies the mutagenic and carcinogenic potential of nanosilver while surface chemistry affects the biosafety of iron oxide nanoparticles - Gábelová, A. (2017)
Nowadays engineered nanomaterials (ENMs) are increasingly used in a wide range of commercial products and biomedical applications. Despite this, the knowledge of human potential health risk as well as comprehensive biological and toxicological information is still limited. We have investigated the capacity of two frequently used metallic ENMs, nanosilver and magnetite nanoparticles (MNPs), to induce thymidine kinase (Tk+/−) mutations in L5178Y mouse lymphoma cells and transformed foci in Bhas 42 cells. Two types of nanosilver, spherical nanoparticles (AgNM300) and fibrous (AgNM302) nanorods/wires, and MNPs differing in surface modifications [MNPs coated with sodium oleate (SO-MNPs), MNPs coated with SO + polyethylene glycol (SO-PEG-MNPs) and MNPs coated with SO + PEG + poly(lactide-co-glycolic acid) SO-PEG-PLGA-MNPs] were included in this study. Spherical AgNM300 showed neither mutagenic nor carcinogenic potential. In contrast, silver nanorods/wires (AgNM302) increased significantly the number of both gene mutations and transformed foci compared with the control (untreated) cells. Under the same treatment conditions, neither SO-MNPs nor SO-PEG-PLGA-MNPs increased the mutant frequency compared with control cells though an equivocal mutagenic effect was estimated for SOPEG- MNPs. Although SO-MNPs and SO-PEG-MNPs did not show any carcinogenic potential, SO-PEG-PLGA-MNPs increased concentration dependently the number of transformed foci in Bhas 42 cells compared with the control cells. Our results revealed that fibrous shape underlies the mutagenic and carcinogenic potential of nanosilver while surface chemistry affects the biosafety of MNPs. Considering that both nanosilver and MNPs are prospective ENMs for biomedical applications, further toxicological evaluations are warranted to assess comprehensively the biosafety of these nanomaterials.